2010
DOI: 10.1158/1538-7445.am10-918
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 918: Glucuronidation genotypes and nicotine metabolic phenotypes: Importance of UGT2B10 and UGT2B17 knock-out polymorphisms

Abstract: Glucuronidation is an important pathway in the metabolism of nicotine, with ∼28% of urinary nicotine metabolites in the form of glucuronidated compounds. Recent in vitro studies have suggested that the UGTs 2B10 and 2B17 play major roles in nicotine glucuronidation with polymorphisms in both enzymes shown to significantly alter the levels of nicotine-, cotinine-, and trans-3-hydroxy-cotinine (3HC)-glucuronides in human liver microsomes in vitro. In the present study, the relationship between the levels of urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This study is, to our knowledge, the most comprehensive study examining nicotine-N 0 -oxidation by the FMO family of enzymes. Nicotine-N 0 -oxidation is one of the direct detoxification pathways for nicotine, and while it accounts for a mean of 4%-7% of total urinary nicotine metabolites across multiple studies (16,17), data from this study demonstrate that NOX formation may be a critical pathway for nicotine elimination in people with diminished or deficient CYP2A6 activity. Furthermore, results from this study suggest that functional SNPs in FMOs 1, 2, and 3 may play an important role in nicotine metabolism variability in people with diminished or deficient CYP2A6 activity.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This study is, to our knowledge, the most comprehensive study examining nicotine-N 0 -oxidation by the FMO family of enzymes. Nicotine-N 0 -oxidation is one of the direct detoxification pathways for nicotine, and while it accounts for a mean of 4%-7% of total urinary nicotine metabolites across multiple studies (16,17), data from this study demonstrate that NOX formation may be a critical pathway for nicotine elimination in people with diminished or deficient CYP2A6 activity. Furthermore, results from this study suggest that functional SNPs in FMOs 1, 2, and 3 may play an important role in nicotine metabolism variability in people with diminished or deficient CYP2A6 activity.…”
Section: Discussionmentioning
confidence: 70%
“…The Shanghai cohort subjects smoked an average of 15.3 cigarettes/day for 46.5 years as compared with 17.2 cigarettes/day and 31.7 years for the Singapore cohort subjects. In addition to nicotine, eight of its major metabolites (NOX, cotinine-N-oxide, trans-3-hydroxycotinine, nicotine-Nglucuronide, cotinine-N-glucuronide, trans-3 0 -hydroxycotinine-O-glucuronide, and 4-hydroxy-4-(3-pyridyl)-butanoid acid) were quantified in urine samples of the 106 smokers using a previously reported LC/MS method (17).…”
Section: Nicotine Metabolites In the Urine Of Smokersmentioning
confidence: 99%
See 1 more Smart Citation
“…COT is slowly eliminated from plasma with a half-life of 10-27 h (Jarvis et al, 1988), undergoing metabolism by hydroxylation to 3-hydroxy-COT (3HC) (Miki et al, 1996) and N-(hydroxyl-methyl) norcotinine (Brown et al, 2005), glucuronidation to cotinine-Nglucuronide (COT-Gluc) (Chen et al, 2007), and oxidation to COT-N-oxide (COX), accounting for an average of 63, 4, 24, and 9% of cotinine metabolites, respectively, in the urine of Caucasian smokers (Figure 1) (Rangiah et al, 2011). While extensive studies have been performed examining the enzymes responsible for the formation of COT (Miki et al, 1996), N-(hydroxymethyl)-norcotinine (Brown et al, 2005), and COT-Gluc (Chen et al, 2010), no studies have identified the enzymes responsible for COX formation (Yamanaka et al, 2004;Yildiz, 2004).…”
Section: Introductionmentioning
confidence: 99%